Genetic factors and epigenetic mechanisms of longevity: current perspectives. (December 2015) - Lazarus, Jessica; Mather, Karen A; Thalamuthu, Anbupalam; Kwok, John BJ
The exceptional longevity phenotype, defined as living beyond the age of 95, results from complex interactions between environmental and genetic factors. Epigenetic mechanisms, such as DNA methylation and histone modifications, mediate the interaction of these factors. This review will provide an overview of animal model studies used to examine age-related epigenetic modifications. Key human studies will be used to illustrate the progress made in the identification of the genetic loci associated with exceptional longevity, including APOE and FOXO3 and genes/loci that are also differentially methylated between long-lived individuals and younger controls. Future studies should focus on elucidating whether identified longevity genetic loci directly influence epigenetic mechanisms, especially on differentially methylated regions associated with longevity.